Troublemaker [compact disc, unabridged] - Howard, Linda, 1950- (Harper Audio, 2016)
Sent to a remote location in a small West Virginia mountain town to lay low after almost being killed in an ambush, Morgan Yancy finds his attraction to part-time police chief and housemate Isabeau Maran adds an unexpected complication to his life.